Uma proposta de ensino de eletrostática com auxílio do gerador de Van de Graaff - Marcondes, José Vlademir Ribeiro (2017)
This work presents the report of the use of experimental class with the help of the Van de Graaff Generator that seeks to explore the introductory concepts of electrostatics. Based on the constructivist model we followed the assumptions of Meaningful Learning Theory (MLT), with the interaction between theory and practice to make knowledge potentially significant in the cognitive structure of the student, in a methodological proposal appropriate to the reality of the school where the proposal. A teacher support material has been proposed, which includes a didactic and manual organization of the Van De Graaff Generator, as well as some experimental activities to be developed with the generator, which approach and explore the concepts of electrostatics interactively. It is sought, with the support of this material, to stimulate students to understand, question and seek knowledge. The methodological proposal was developed in 3 stages, where the experimental activities were placed in a didactic sequence. The material was applied to students of the third year C, class with 23 high school students of the morning period of the State School Prof. Domingos Ap. Dos Santos, located at square Francisco Clarion - São José II Housing Nucleus, in the city of Rondonópolis / MT. As an instrument of orientation, data collection and evaluation were used a Pre and a Post Test, as well as the Diagram V. The analysis of the collected data had a qualitative character and based on the collected data it is possible to observe indications that the material contributed to The motivation of students and the promotion of Significant Learning of the concepts of electrostatics.